2001
DOI: 10.1046/j.1540-8175.2001.00275.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two‐Dimensional Echocardiography and Pulsed Doppler Tissue Imaging during Dobutamine‐Atropine Stress Testing to Detect Coronary Artery Disease

Abstract: In order to compare the diagnostic accuracy of two-dimensional (2-D) echocardiography and pulsed Doppler tissue imaging (pDTI) during dobutamine-atropine stress testing (DAST) to detect significant coronary lesions, 41 patients underwent DAST (up to 40 microg/k/min of dobutamine with additional atropine during submaximal heart rate responses) and coronary angiography. Pulsed Doppler tissue sampling of territories corresponding to the left anterior descending (LAD), left circumflex (LCx), and right coronary art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…22 We found that in 21% of patients, the peak stress e 0 velocity could not be measured and that in a higher percentage of the patients with ischemia, the peak stress E/e 0 and E/A ratios could not be measured. This observation might indicate a relationship between the fusion of E and A waves and stress-induced ischemia.…”
Section: Feasibility Of Dtimentioning
confidence: 66%
“…22 We found that in 21% of patients, the peak stress e 0 velocity could not be measured and that in a higher percentage of the patients with ischemia, the peak stress E/e 0 and E/A ratios could not be measured. This observation might indicate a relationship between the fusion of E and A waves and stress-induced ischemia.…”
Section: Feasibility Of Dtimentioning
confidence: 66%
“…No estágio da baixa dose de dobutamina, as ondas E e A foram adquiridas em 86% dos exames no grupo placebo, 93% dos exames no grupo estatina e as ondas e', a' e s em 100% dos exames em ambos os grupos . No pico do estresse, conforme relatado na literatura 92 , tornouse muito frequente a fusão das ondas E e A ou das ondas e' e a' devido ao aumento da frequência cardíaca (53% fusão E/A e 25% fusão e'/a'). Dessa forma, os índices de Doppler adquiridos neste estágio foram excluídos.…”
Section: Factibilidade De Aquisição Das Variáveis De Doppler Ao Longounclassified